Biochemical aspects of a zinc-polyphenolic compound on the maize-Colletotrichum graminicola interaction - Tibolla, Tiago da Silva (Universidade Federal de Viçosa, 2025)
Anthracnose, caused by the hemibiotrophic fungus Colletotrichum graminicola, is one of the major diseases affecting maize production globally. In this context, new alternatives for disease control need to be investigated. In this study, the hypothesis that maize plants sprayed with Semia? [zinc (Zn) (20%) and nitrogen (N) (1%) complexed with a plant-derived pool of polyphenols (10%); referred to as induced resistance (IR) stimulus] could hamper the infection of maize leaves by C. graminicola was investigated. The IR stimulus-sprayed and water-sprayed plants (control) were either non-inoculated or inoculated with C. graminicola. Leaf samples were collected at 2, 4, 6 and 12 days after inoculation for biochemical analysis. Compared to water-sprayed and infected plants, the foliar concentration of Zn, the incubation period and the latent period significantly increased by 159, 136 and 81%, respectively, while the area under anthracnose progress curve significantly decreased by 74% for IR stimulus-sprayed and infected ones. At the biochemical level, increased activities of defense-related (chitinase, ß-1,3-glucanase, phenylalanine ammonia-lyase, polyphenol oxidase and lipoxygenase) and antioxidative (ascorbate peroxidase, catalase, glutathione reductase, peroxidase and superoxide dismutase) enzymes were obtained for IR stimulus-sprayed and infected plants in contrast to water-sprayed and infected ones. These findings highlight the potential of using this IR stimulus for anthracnose management with less dependence on fungicide spray and, consequently, towards a more sustainable agriculture. Keywords: Zea mays ; antioxidative metabolism; host defense reactions; induced resistance; mineral nutrition

A antracnose, causada pelo fungo hemibiotrófico Colletotrichum graminicola, é uma das principais doenças que afetam a produção de milho em todo o mundo. Nesse contexto, novas alternativas para o controle da doença precisam ser investigadas. Para esse estudo, foi testada a hipótese de que plantas de milho pulverizadas com Semia® [zinco (Zn) (20%) e nitrogênio (N) (1%) complexado com um polifenóis obtidos de plantas (10%); referido como estimulador da resistência induzida (ERI)] poderiam afetar a infecção das folhas de milho por C. graminicola. Plantas pulverizadas com água (controle) ou com o ERI foram inoculadas ou não com C. graminicola. Amostras foliares foram coletadas aos 2, 4, 6 e 12 dias após inoculação para as análises bioquímicas. Em comparação com as plantas infectadas e pulverizadas com água, aquelas tratadas com o ERI apresentaram aumentos significativos na concentração foliar de Zn (159%), no período de incubação (136%) e no período latente (81%), além de uma redução significativa de 74% na área abaixo da curva do progresso da antracnose. No nível bioquímico, as plantas tratadas com ERI e infectadas apresentaram aumentos significativos nas atividades das enzimas relacionadas com defesa (quitinase, ß-1,3-glucanase, fenilalanina amônia-liase, polifenoloxidase e lipoxigenase) e antioxidantes (ascorbato peroxidase, catalase, glutationa redutase, peroxidase e superóxido dismutase) em comparação com plantas infectadas e pulverizadas com água. Esses resultados destacam o potencial do uso desse ERI para o manejo da antracnose, com menor dependência da aplicação de fungicidas e, consequentemente, promovendo uma agricultura mais sustentável. Palavras-chave: Zea mays ; indução de resistência; metabolismo antioxidativo; nutrição mineral; reações de defesa da planta.
Aspectos bioquímicos de um composto de zinco-polifenólico na interação entre milho e Colletotrichum graminicola
Keywords: Zea mays; Milho - Resistência a doenças e pragas; Nutrição mineral; Antracnose; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::FITOPATOLOGIA